Dynamics of long-term policy implementation of Eco-transformation of industrial parks in China. (20th January 2021) - Zhao, Ruitong; Peng, Hao; Jiao, Wenting
Abstract : The concept of Ecological Transformation of Industrial Parks (ETIPs) has been translated into diverse policy practices worldwide. To gain insights into the dynamics of adapting novel policy concepts in new contexts and further safeguarding them for durable and effective policy outcomes of ETIPs, we built on policy translation framework and adopted Event Sequence Analysis to reconstruct and compare successive policy translation patterns of Eco-industrial Park (EIP) and Circular Economy Industrial Park (CEIP) in China. The results show that both the policies manifested the sequential dynamics of 1) adapting the novel concepts in new contexts through the single-agency approach in the early phase and 2) stabilizing policy outputs gradually to achieve effective outcomes through the multi-actor cooperation in the late phase. A key policy implication is that the sequential features are useful for countries as "latecomers" of ETIPs to detect the signals of emerging local initiatives and facilitating them into nation-wide practices. Importantly, this process may take decades and requires the patience of policy makers.